Design and Analysis of a Hexagonal Patch Antenna Operating at 3.5 GHz for Wireless Communication Applications - Yudi Barnadi; Ajeng Mayang Kurniaviep Sugeng; Ase Suryana; Arief Budi Santiko (LPPM Universitas Negeri Semarang, 2024)
Microstrip antennas are widely recognized for their compact structure, low profile, and ease of fabrication, making them highly suitable for modern wireless communication systems. Traditionally, these antennas incorporate a rectangular metallic patch as the radiating element. In this study, a novel microstrip antenna design featuring a hexagonal metal patch is proposed, specifically optimized to resonate at 3.5 GHz, a frequency band allocated for 5G wireless communication applications. The antenna is constructed on an F4BMX220 substrate with a thickness of 1.5 mm, chosen for its favorable dielectric properties and mechanical stability. The feeding mechanism employs an inset-fed microstrip line, enabling better impedance matching and improved power transfer. A full ground plane is used on the underside of the substrate to enhance isolation and minimize back radiation. The complete design, simulation, and optimization processes are carried out using CST Studio Suite, a professional electromagnetic simulation tool. Key performance parameters such as return loss (S11), directivity, and gain are thoroughly analyzed. The design aims to achieve an S11 value below -10 dB, ensuring efficient radiation at the target frequency. With its optimized structure and favorable performance, the proposed antenna serves as a promising candidate for integration into next-generation 5G communication systems. Based on the fabricated prototype, the antenna demonstrates a gain of 4.5 dBi and a bandwidth of 24 MHz.